(untitled) (Global Journal of Science Frontier Research, 2015)
New metal complexes of the ligand (HL) 2-[1H-Pyrrol-2-ylimino methyl]-5-phenyl-1, 3,4-oxadiazol with the metal ions Co(II), Ni(II) and Cu(II), were prepared in alcoholic medium. The Schiff bases were condensed by using [Pyrrolcarboxaldehyde] with[2-amino-5-(phenyl-1, 3,4-oxadiazole] in alcoholice medium. As the Schiff baseprepared was tridentate ligand, it was used for forming complexes with Co+2, Ni+2, Cu +2 and Zn+2 ions of type M (HL)2. All the synthesized Schiff base and their metal complexes were characterized by FTIR Spectroscopy, Electronic Spectroscopy, Elemental Analysis,